La pantalla como tablero apuntes para el uso de la imagen audiovisual en el aula universitaria (2005)
This research becomes an effort of IMAGO group for advancing in its contributions to the complex and rich relation between communication and education. It collects ideas that the authors have developed in the last years in the field of image and, particularly, the developing of the image in classrooms. This text goes away from deep conceptualization and focuses in offering a tool for using image as a didactic mediation in the educative processes. In this way, authors use elements of the video and its different didactic use possibilities. They also put into operation a brief conception of didactics, in order to bring the reader close to the concepts from which their proposal has been worked. Based on this, the research offers a step by step o an organized process which offers the reader some important keys to take advantage of the audiovisual image in methodologies and educative didactics. Video in the classroom before, currently, and after become keys that playing to the simile of video production (Pre-production, production, post-production) allow state the didactic proposal.